Non-alcoholic Fatty Liver Disease with Type 2 DM in Rural and Urban Areas in Bangladesh (TAJ: Journal of Teachers Association, 2023)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is a chronic liver condition that affects up to one-third of adults in developed nations. NAFLD refers to a group of non-alcoholic diseases that are histologically and clinically distinct. Fatty liver (NAFL, steatosis hepatitis) and steatohepatitis can lead to cirrhosis and rare cases of hepatocellular carcinoma.Materials and Methods: This was a cross-sectional descriptive study conducted in the medicine department, Rajshahi medical college, Rajshahi, among ninety-one T2DM patients. The study population included outdoor patients as well as hospitalized consecutive 91 patients (50 Urban and 41 Rural) in the medicine department with type 2 DM diagnosed according to the American Diabetes Association (ADA) 2011 criteria. NAFLD was detected and graded using abdominal ultrasonography and blood pressure, BMI, waist circumference, HbA1c, lipid profile, and liver function tests. All data were analyzed by SPSS 16, and p-value